Pengenalan Motif Tenun Karaja Lamboya melalui Pemanfaatan Fitur Shaping pada Peserta Didik MAN Sumba Barat - Mitra Permata Ayu; Dian Fransiska Ledi; Ardiyanto Dapadeda; Marianus R. lasan; Andreas Ariyanto Rangga (PDPI, 2026)
Digital training is an urgent approach in education in the digital era, one of which is how to utilize the shaping feature in Microsoft Word. The shaping feature is one of the features in the insert menu that has the function of making documents more attractive with various options. Utilization of the shaping feature can be used to sketch simple woven motifs, namely Karaja weaving. Karaja ikat weaving originates from West Sumba Regency. The purpose of community service is to introduce students to Karaja weaving motifs through simple sketches using the shaping feature so that students not only understand the basic forms and patterns of motifs, but are also able to develop visual skills, creativity, and numeracy literacy based on local culture. The results of the activity show that students not only gain knowledge about Karaja Lamboya Weaving motifs, but are also able to apply the shaping feature to create simple sketches of woven motifs. In addition, this training activity provides real benefits for students, especially in integrating local cultural elements with the use of technology.